2012
DOI: 10.1007/s12325-012-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid is an Important Predictor for Hypertensive Early Atherosclerosis

Abstract: Hyperuricemia is an independent predictor for early atherosclerosis in hypertensive subjects with normal renal function. Therefore, the optimal control of UA may provide further benefits in preventing atherosclerosis and hypertensive end-organ injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 41 publications
2
16
0
1
Order By: Relevance
“…Surrogate markers of atherosclerosis shown to have an association with hyperuricemia include carotid intima-media thickness (C-IMT) [11, 3236], ankle brachial index [34], coronary artery calcification [37], and brachial-ankle pulse wave velocity (baPWV) [38]. In addition, many studies suggest an independent effect of elevated serum uric acid on atherosclerosis as measured by these surrogate markers after adjusting for the influence of metabolic syndrome and other factors [11, 33, 35, 39]. In particular, there is evidence that uric acid has direct effects on key processes involved in endothelial function and vascular remodeling [40].…”
Section: Hyperuricemia and Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Surrogate markers of atherosclerosis shown to have an association with hyperuricemia include carotid intima-media thickness (C-IMT) [11, 3236], ankle brachial index [34], coronary artery calcification [37], and brachial-ankle pulse wave velocity (baPWV) [38]. In addition, many studies suggest an independent effect of elevated serum uric acid on atherosclerosis as measured by these surrogate markers after adjusting for the influence of metabolic syndrome and other factors [11, 33, 35, 39]. In particular, there is evidence that uric acid has direct effects on key processes involved in endothelial function and vascular remodeling [40].…”
Section: Hyperuricemia and Atherosclerosismentioning
confidence: 99%
“…For example, hypertensive hyperuricemic patients have higher levels of BMI, C-IMT, fasting plasma glucose, UA, hs-CRP, and proteinuria as compared with hypertensive normouricemic subjects. Hyperuricemia, per se , was found to be an independent predictor for atherosclerosis in patients with hypertension [33]. In another clinical study, serum uric acid was found to be associated with subclinical atherosclerosis in men with type II diabetes mellitus [34, 49].…”
Section: Hyperuricemia and Atherosclerosismentioning
confidence: 99%
“…The carotid intima-media thickness (CIMT), assessed noninvasively using ultrasonography, has been validated to be a sensitive marker of atherosclerosis and is directly associated with an increased risk of cardiovascular disease 10) . Previous studies have shown the uric acid level to be positively associated with the CIMT in various specific populations, including patients with hypertension 11) or diabetes mellitus 12) and postmenopausal women 13) . However, limited data are available regarding the relationship between the uric acid level and CIMT in the general population.…”
Section: Questionnaire Data and Biochemical Measurementsmentioning
confidence: 99%
“…Исследование риска развития атеросклероза (исследование ARIC) [21] показало, что уровень МК в значительной степени предопределяет увеличение толщины интима-медиа сонных артерий при проведении ультразвукового исследования. Впоследствии R. Mutluay et al (2012) сообщили, что гиперурикемия является независимым предиктором раннего атеросклероза у гипертоников с нормальной функцией почек [22]. Аналогичные результаты атерогенной роли МК в патофизиологии ССЗ были получены A.F.…”
Section: гиперурикемия и повреждение органов-мишенейunclassified